Minimizing Food Safety Hazards for Organic Growers - Amy Simonne; Danielle Treadwell (EDIS)
FCS-8872, a 9-page fact sheet by Amy Simonne and Danielle Treadwell, integrates the key requirements of the Food and Drug Administration Guide to Minimize Microbial Food Safety Hazards for Fresh Fruits and Vegetables (FDA GAPs) and the USDA National Organic Program (NOP) in order to emphasize the areas in which producers can most significantly reduce the food safety risk for their consumers. Includes references. Published by the Department of Family, Youth, and Community Sciences, September 2008.